Hazard Analysis of Weather Conditions on Distribution Transformer Failures via Cox Proportional Hazard Model - Cheonkyu Park; Chongeun Cho; Do-In Kim (IEEE Access)
As the operational years of power facilities increase, the importance of accurately assessing the remaining lifespan or risk of failures of distribution transformers for the stable power supply has also grown. However, unlike the typical transformer failures, it is not quantified that the failures are also influenced by weather conditions such as temperature, humidity, precipitation, etc. In this regard, we propose the method for investigating the impact of the weather conditions on the failures of distribution transformers to improve the asset management. By employing survival analysis approach, frameworks are employed to quantify the spatial influence of weather conditions on distribution transformer failures, and the weather risk factors are integrated into lifespan indicators to improve maintenance strategies and reliability assessments. Distribution transformer failure cases of over 11 years in South Korea and the corresponding historical weather conditions are configured to enable the survival analysis and derive the meaningful real-world analysis results. Specifically, weather data are quantified and interpolated to configure the spatial data. The notable results underline quantifying significant impact of high summer temperature and humidity in term of hazard ratios. These findings indicate that incorporating historical weather data into asset management indices can significantly enhance the accuracy of transformer lifespan predictions and inform maintenance planning. This study represents the first long-term survival analysis correlating historical weather conditions with transformer failures and provides a guideline for improving power-facility management in the context of environmental changes.